Surgical metabolism : the metabolic care of the surgical patient - Rosenbaum, Stanley H.; Davis, Kimberly A. (Springer New York, 2014)
This volume is a comprehensive, state-of-the-art review for clinicians with an interest in the peri-operative nutritional management of all surgical patients. The text reviews normal physiology, the pathophysiology of starvation and surgical stressors, and focuses on appropriate nutritional repletion for various common disease states. Specifically, the text addresses the severe metabolic demands created by systemic inflammation, infection, and major insults such as trauma and burns. In addition, the book addresses the growing problem of obesity in surgical populations, including appropriate strategies directed towards the metabolic management of these patients. The text is designed for clinicians across levels of training and provides clear and concise evidence based guidelines for the metabolic management and nutritional support of the surgical patient. Written by experts in the field, Surgical Metabolism: The Metabolic Care of the Surgical Patient is a valuable resource for all clinicians involved in the care of the critically ill.